Urban Autonomy and Political Negotiation. The Difficult Articulation of a State Taxation in the Kingdom of Seville, 1474-1504 (Edad Media. Revista de Historia, 2020)
Historically, historiography has focused on the fiscal freedoms of the Castilian cities as a projection of the complex debate about what the structure of the State should be and how the relations between the central power and the local powers should be articulated. Beyond these considerations, which in their extreme positions have come to exalt or deny freedom, we will aim in this article to provide a more measured view of the relationships between king and kingdom through the documentation preserved for the space of the former kingdom of Seville at the time of the Catholic Monarchs. Our research shows that those relationships were marked by the growing confluence between the royal and municipal taxation and propelled intense negotiations between the throne and the cities.
Keywords: Municipalities; Monarchy; Freedom; Privileges; Cortes